Analysis of Social Entrepreneurship Competencies for Non-Formal Education Improvement - Adi Irvansyah; Pudji Muljono; Anna Fatchiya; Dwi Sadono (International Journal of Science and Society, 2023)
Entrepreneurial skills are necessary competencies for non-formal education managers. However, the development of social entrepreneurship skills in non-formal education has not received sufficient attention. This study aims to evaluate social entrepreneurship competencies and identify the factors and processes of non-formal education. Specifically, the research aims to analyze social entrepreneurship competencies among managers of non-formal education. The research method used is a literature review that collects data from relevant sources. The analysis shows that social entrepreneurship competencies required by non-formal education managers include creativity, adaptability, self-confidence, networking, understanding of social issues, and managerial skills. Additionally, non-formal education managers need knowledge and skills in financial management, marketing, and collaboration with other parties. This study contributes to strengthening the role of non-formal education managers in increasing the contribution of non-formal education institutions to society. The study's results can be a reference for non-formal education managers to improve their social competence.